Electrocatalytic Activity for o2 Reduction of Unsubstituted and Perchlorinated Iron Phthalocyanines Adsorbed on Amino-Terminated Multiwalled Carbon Nanotubes Deposited on Glassy Carbon Electrodes - Zagal-Moya, J; Zagal-Moya, J; Silva-Rojas, J; Silva-Rojas, J (Sociedad Chilena de Quimica, 2014)
Amino-functionalized multiwalled carbon nanotubes (MWCNT-NH2) were modified with Fe phthalocyanine (FePc) and perchlorinated Fe phthalocyanine (16(Cl)FePc) and deposited on glassy carbon electrodes (GCE). The electrocatalytic activity of these hybrid electrodes was examined for the reduction of molecular oxygen in alkaline media (0.2 M NaOH) using stationary and rotating disk electrodes. Electrodes containing 16(Cl)FePc are more active than those containing FePc. Electrodes containing CNTs are more active than electrodes without CNTs but the higher activity can be attributed to a greater real surface area, compared CGEs and not necessarily to a catalytic effect. © 2014, Sociedad Chilena de Quimica. All rights reserved.